"Adjustment to life in a nursing home", the process of relocation : a grounded theory study - Mandville-Anstey, Sue Ann, 1971- (2002)
Thesis (M.N.)--Memorial University of Newfoundland, 2002. School of Nursing Bibliography: leaves 97-104. Research into the relocation of the elderly from the community to long term care has been well documented as a major life change for this population, one that may have many physical, social, and cognitive implications. Some research documents the positive implications such as an increased sense of security, increased social contacts, and better physical well being. Contrary to this, other research suggests negative implications such as anxiety, depression, and loss of independence. -- Grounded theory methodology was used to explore the process of relocation and subsequent adjustment to a nursing home among elderly adults four to six months after admission. Six females and three males were interviewed and data analysis was conducted to determine the common themes that existed in the individuals' experiences of their adjustment. -- Three main stages of relocation were identified: preparing for the move, moving to the nursing home, and settling in on a more permanent basis. Within each of these three stages a number of phases were identified and the interrelationships between these phases allowed the researcher to identify similarities and differences among the participants with regards to their adjustment to the relocation to the nursing home. -- The findings of this study emphasized the variation in the psychological adjustment to nursing home life including factors that helped or hindered the adjustment process. The results of this study supported the literature in the identification of interventions to help ease this transition. The research also identified new insights into the process of relocation and how adjustment may be experienced by members of this population.